2012
DOI: 10.1177/0020872812447625
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on research: Families affected by counter-terrorism in the UK

Abstract: Following the terrorist attacks on New York and London, the counterterrorism legislation in the UK strengthened surveillance and national security and led to the incarceration of many Muslim men. Whilst the treatment of prisoners and detainees received considerable attention in public debate, the families that are left behind have been neglected by politicians, academics, the media and service providers alike. This article reflects on the experiences of conducting a small exploratory study amongst such familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Family members of radicalized individuals can suffer internalizing problems such as anxiety and depression (Guru, 2012a(Guru, , 2012b. This might cause a polyvictimization process that could increase the risk of radicalization of the previously non-radicalized family members over the lifespan.…”
Section: Impact Of Violent Radicalization On Familiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Family members of radicalized individuals can suffer internalizing problems such as anxiety and depression (Guru, 2012a(Guru, , 2012b. This might cause a polyvictimization process that could increase the risk of radicalization of the previously non-radicalized family members over the lifespan.…”
Section: Impact Of Violent Radicalization On Familiesmentioning
confidence: 99%
“…Thus, studying the impact of radicalization on family is urgently needed. This is especially true given that some qualitative studies found that families of radicalized individuals are highly affected (Guru, 2012a(Guru, , 2012b. Our systematic review included a wide range The included studies were mostly cross-sectional, and it was impossible to establish which family-related factors were causal or preceded radicalization.…”
Section: Implications For Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Al Mikhamresh et al (2012), researching social work activities with Iraqi refugees in Jordan, highlight the need for politically competent social work practice, in the sense of having to understand well the 'political map' in the situation and use this understanding to benefit clients. Guru (2012) refers to the dilemma of the researcher attempting to work with families of young Moslem men accused of engaging in terrorist activities. This research sympathizes with the families and wishes to understand better their context, but is not sure how ethical it is to research such families at the crisis stage in which their lives are embedded, while the researchers simultaneously experience difficulties in getting ethical permission to carry out this research on the grounds of potential risk to them.…”
Section: Researching Armed Conflictmentioning
confidence: 99%